Graphene/Gold Nanocomposites-Based Thin Films as an Enhanced Sensing Platform for Voltammetric Detection of Cr(VI) Ions - Chella Santhosh; Murugan Saranya; Rajendran Ramachandran; Sathiyanathan Felix; Venugopal Velmurugan; Andrews Nirmala Grace (Journal of Nanotechnology)
A highly sensitive and selective Cr(VI) sensor with graphene-based nanocomposites film as an enhanced sensing platform is reported. The detection of chromium species is a challenging task because of the different possible oxidation states in which the element can occur. The sensing film was developed by homogenously distributing Au nanoparticles (AuNPs) onto the two-dimensional (2D) graphene nanosheet matrix by electrochemical method. Such nanostructured composite film platforms combine the advantages of AuNPs and graphene nanosheets because of the synergistic effect between them. This effect greatly facilitates the electron-transfer processes and the sensing behavior for Cr(VI) detection, leading to a remarkably improved sensitivity and selectivity. The interference from other heavy metal ions is studied in detail. Such sensing elements are very promising for practical environmental monitoring applications.